Innovative teaching and assessment during covid-19 (2021)
As numerous countries of the world experienced lockdown, due to the COVID-19 pandemic schools in Nigeria were closed in March 2020. Though schools started partial-reopening seven months after the lockdown in September, severe restrictions remain the order of the day in schools, as it is in some other sectors like sports. Any assurance on when the restrictions will completely be removed appears to be barely feasible at the moment. As a result of the situation, course facilitators in Nigeria were only able to sustain minimal face to face interactions with learners, and they were forced to subscribe to online instructional delivery which poses some substantial predicaments. In view of this, the paper investigates innovative teaching and assessment (selection of YouTube videos, email-based consultation, online mock quizzes and Google classroom) strategies during COVID-19. Different teaching and assessment methods were discussed, and the following lessons from COVID-19 circumstance were highlighted: The Pandemic lockdown offered learners opportunities to access different learning materials to aid their study of the subject area; learners acknowledge the physical presence of visual instructors for their learning of the course resources; another lesson is the significance of a precise and dependable work-book for the course delivered. The paper then recommends that academic organisation should embrace innovation in technology in order to tackle the issues of pressure on server, inadequate computer gadgets, and lack of technical know-how in software installations. Similarly, institution should have an alternative strategy in place to combat the challenges posed by the pandemic without prejudice to students learning and in readiness for future crisis.